Intimate partner violence and risk of HIV infection in Pakistan (Italian Journal of Public Health, 2011)
Globally, violence against women is increasing, and is currently recognized as a major public health problem with significant consequences to women’s health. The detrimental health effects such as injury, chronic pain, gastrointestinal, and gynecological signs including sexually-transmitted diseases, depression, and post-traumatic stress disorder have been observed in abused women. Violence, like in other Asian countries, is a huge problem in Pakistan
Keywords: partner violence; HIV infection; Pakistan